Poenostavljeno zmanjšanje osnovnega kapitala v d. o. o. in GmbH - Ćaćić, Nino (Podjetje in delo, 2020)
The author discusses the procedure of simplified capital reduction in a company with limited liability, in both Slovenian and German law. This represents a transaction on the passive side of the balance sheet, with assets remaining unchanged. The purpose of this transaction is recapitalisation of the company. This recapitalisation can be accelerated if the simplified capital reduction is linked to the institute of rebound effect and capital increase. The, the company gains extra assets.
Keywords: balance law; bilančno pravo; d. o. o.; družba z omejeno odgovornostjo; GmbH; osnovni kapital; poenostavljeno zmanjšanje osnovnega kapitala; povratni učinek; rebound effect; simplified capital reduction